Psychometric Properties of the Behavioral Emotion Regulation Questionnaire (BERQ) in Peruvian Adolescents - Navarro-Loli, Jhonatan S. (2025)
The behavioral strategies for emotional regulation in adolescents are associated with mental health issues such as depression, making it important to have tools that allow for their assessment. This study uses an instrumental design and aims to evaluate the psychometric properties of the Behavioral Emotion Regulation Questionnaire (BERQ) in Peruvian adolescents. The sample was selected using a non-probabilistic convenience sampling method and consisted of 392 adolescents aged 14 to 17 years (M = 15.75; SD = .85), with 52.5% being male. Through exploratory structural equation modeling, it was found that the original five-factor structure was replicated (CFI = .988; RMSEA = .045, 90% CI .031, .058; WRMR = .429), and each factor achieved acceptable reliability values through Cronbach’s alpha and McDonald’s omega coefficients. Additionally, it was found that only withdrawal (β = −.49), active coping (β = −.21), and ignoring the problem (β = .24) are statistically significant predictors of depression. It is concluded that the instrument can be used in research and as support for professionals in the evaluation of the construct.